Epicardial Ablation of Focal Atrial Tachycardia Arising From Left Atrial Appendage in Children - Hanumandla, Abdhija (Indian Heart Rhythm Society, 2014)
Focal left atrial tachycardia (FLAT) although a common cause of supraventricular tachycardia(SVT) among children, the one's arising from left atrial appendage (LAA) present a unique challenge for successful ablation because of anatomical location. We present two children with FLAT arising from the epicardial LAA, successfully mapped and ablated through percutaneuous epicardial approach.